The Relationship Between Academic Service Quality and Employee Job Satisfaction: Evidence from Cambodian Public Universities - Sophea Menh; Sokean Kouy; Visalbot Pok; Sarom Mok (Journal of Mathematics Instruction, Social Research and Opinion, 2025)
Research exploring the perceptions of public university employees in Cambodia regarding job satisfaction and academic service quality revealed significant insights. Using a quantitative design with a sample of 336 staff from three Phnom Penh universities, the study found that employees reported a high perception of both their job satisfaction and the academic services they provide. On average, staff felt more satisfied with their jobs than they rated the quality of academic services, although both were perceived positively. This suggests that job satisfaction is a slightly stronger factor. A key finding was the confirmed positive relationship between the two variables, indicating that the perception of academic service quality increases as job satisfaction increases. This correlation highlights the crucial link between employee well-being and the quality of education services. The research, driven by the need to enhance the education sector, provides valuable insights into employee morale and the current state of academic services within the Cambodian public university system, underscoring the importance of focusing on staff satisfaction as a strategy for improving educational offerings.